Protocolos de Ensino Baseado em equivalência em estudantes universitários: efeitos da estrutura e do tipo de treino - Mali, Gabriel Lucas (2024)
Equivalence-Based Teaching (EBI) is a teaching protocol that has the stimulus equivalence paradigm as its guiding principle. A growing area of interest in EBI research is its application to teaching academic content in a university context. The present study implemented EBI protocols for teaching neuroanatomy to university students and verified the formation and maintenance of equivalence classes as a function of protocol structure parameters (one-to-many and many-to-one) and type of matching procedure (simultaneous matching to sample and delayed matching to sample). Participants were 48 university students who were subjected to an EBI protocol with a simple-to-complex training arrangement to establish four equivalence classes with four members each. The members of these classes were: written name of the brain structure (stimuli A), image of the brain structure (stimuli B), description of the structure's function (stimuli C), and description of what damage to the structure can cause (stimuli D). Participants were divided into four groups: group 1 was exposed to an EBI with a one-to-many structure and simultaneous matching to sample; group 2 was exposed to an EBI with a one-to-many structure and the delayed matching to sample, group 3 was exposed to an EBI with a many-to-one structure and simultaneous matching to sample, and group 4 was exposed to an EBI with a many-to-one structure and delayed matching to sample. At the end, participants responded to a social validity questionnaire regarding the EBI procedure. There were no significant differences between groups and between parameters when analyzing the: (1) number of participants in each group who reached the criterion of 89.6% correct answers in the mixed test in the first exposure after teaching (i.e., without need for retraining); (2) average percentage of correct answers in the final mixed test for each group; (3) average time and attempts required to form an equivalence class for each group, and (4) the percentage of participants in each group reached the criterion of 89.6% correct answers in the maintenance test. However, participants who performed the protocol with the delayed procedure obtained a greater number of correct answers in the maintenance test and the use of the procedure produced less variability between the participants' performances. The results answer one basic and one applied research question, reporting that the delayed matching had a positive effect on maintaining equivalence and, thus, indicating this parameter as the most appropriate to be used in EBI protocols in an academic context. It is discussed how different training parameters affect participant performance and how EBI can be implanted in an academic context.